Gamma passing rate evaluation for IMRT and VMAT techniques based on gantry angles - Ummu Mar'atu Zahro; Fatimatuz Zahroh; Fiki Hurum Maqsuroh; Wahyu Edy Wibowo (Journal of Physics: Theories and Applications, 2025)
Introduction: The accuracy of radiation dose delivery in advanced techniques such as Intensity Modulated Radiation Therapy (IMRT) and Volumetric Modulated Arc Therapy (VMAT) is highly dependent on the consistency of gantry angle performance. This study aims to evaluate the effect of gantry angle variations on the gamma passing rate (GPR) in IMRT and VMAT treatment plans. Methods: IMRT and VMAT plans were created using the Monaco Treatment Planning System on a homogeneous slab phantom and delivered within a range of gantry angles, including 90°, 180°, 270°, and 360°. Measurements were performed using the 2D array PTW Octavius 1500 that delivered by Linac Elekta Synergy and analyzed with the Verisoft software, applying a 2%/2 mm gamma index with a 10% threshold and a 97% gamma passing rate criterion. Results: All plans achieved GPR above 97%. VMAT demonstrated higher GPR values than IMRT at gantry angles of 90°, 180°, 270°, with the largest difference of 0.8% observed at 270°. IMRT showed a slightly higher GRP value than VMAT at range gantry 360° with a difference of 0.1%.  Conclusion: The higher GPR value observed in VMAT indicates greater stability in relation to gantry angle variations. Although, IMRT performed slightly better at 360°, the difference was minimal. In general, gantry angle dependence was observed in both techniques, but the variation was not clinically significant.